Perubahan Fungsi Tarian Tummour Pada Suku Mbaham Matta - Reni F Hindom; Yuliana Yuliana; Agustinus Wenehen (CENDERAWASIH: Jurnal Antropologi Papua, 2020)
This article aims to describe and analyze the changes in the function of the Mbaham Matta tribe's ‘tummour’ dance in the past and the present and to find out what efforts were made to be able to maintain the ‘Tummour’ dance of the Mbaham Matta tribe in Fakfak Regency in general. This research is qualitative using data collection techniques through interviews, observation, and documentation. The research results show that the ‘tummour’ dance in the past was used as traditional rituals, traditional parties, to gather the masses, to summon ancestral spirits, to dance the victory of the war and to stem the coming dangers. The change in the function of the ‘tummour’ dance occurred because of the entry of religion and government. Changes that occur are not only in the function of the ‘tummour’ dance, but the attributes used have also changed. Then, the efforts made so that the ‘Tummour’ dance can survive include opening a dance studio and preserving the ‘Tummour’ dance through socialization (transfer of knowledge) or introducing it to the younger generation.